Combined anti‐PD‐1 and anti‐CTLA‐4 checkpoint blockade: Treatment of melanoma and immune mechanisms of action. Issue 3 (23rd February 2021) - Willsmore, Zena N.; Coumbe, Ben G. T.; Crescioli, Silvia; Reci, Sara; Gupta, Ayushi; Harris, Robert J.; Chenoweth, Alicia; Chauhan, Jitesh; Bax, Heather J.; McCraw, Alexa; Cheung, Anthony; Osborn, Gabriel; et al.
Abstract: Cytotoxic T‐lymphocyte associated protein‐4 (CTLA‐4) and the Programmed Death Receptor 1 (PD‐1) are immune checkpoint molecules that are well‐established targets of antibody immunotherapies for the management of malignant melanoma. The monoclonal antibodies, Ipilimumab, Pembrolizumab, and Nivolumab, designed to interfere with T cell inhibitory signals to activate immune responses against tumors, were originally approved as monotherapy. Treatment with a combination of immune checkpoint inhibitors may improve outcomes compared to monotherapy in certain patient groups and these clinical benefits may be derived from unique immune mechanisms of action. However, treatment with checkpoint inhibitor combinations also present significant clinical challenges and increased rates of immune‐related adverse events. In this review, we discuss the potential mechanisms attributed to single and combined checkpoint inhibitor immunotherapies and clinical experience with their use. Abstract : Combination checkpoint inhibitor therapy with the anti‐PD‐1 Nivolumab and anti‐CTLA‐4 Ipilimumab antibodies is approved in advanced melanoma. This may offer enhanced efficacy over single agent treatments but is associated with toxicity. Herein, we summarize evidence for the potential merits, immunological mechanisms, and clinical challenges of combination treatment compared with monotherapy.